2019
DOI: 10.3390/plants8070195
|View full text |Cite
|
Sign up to set email alerts
|

Ozone Tolerance Found in Aegilops tauschii and Primary Synthetic Hexaploid Wheat

Abstract: Modern wheat cultivars are increasingly sensitive to ground level ozone, with 7–10% mean yield reductions in the northern hemisphere. In this study, three of the genome donors of bread wheat, Triticum urartu (AA), T. dicoccoides (AABB), and Aegilops tauschii (DD) along with a modern wheat cultivar (T. aestivum ‘Skyfall’), a 1970s cultivar (T. aestivum ‘Maris Dove’), and a line of primary Synthetic Hexaploid Wheat were grown in 6 L pots of sandy loam soil in solardomes (Bangor, North Wales) and exposed to low (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…In a further screening experiment with 20 different wheat genotypes, they concluded that ozone tolerance may be related to the breeding method (hybrids being more sensitive), while the ozone concentration at the breeding site did not play a significant role (Biswas et al, 2009). Others reported chamber fumigation experiments, in which the wild ancestor of bread wheat, Aegilops tauschii , was described as ozone‐sensitive and synthetic hexaploid wheat was rather tolerant (Brewster, Hayes, & Fenner, 2019). In addition, different studies tested the ozone responses of a limited number (usually two) of wheat genotypes that were described as tolerant or sensitive (e.g., Feng et al, 2010; Feng, Pang, Kobayashi, Zhu, & Ort, 2011; Hansen, Hauggaard‐Nielsen, Launay, Rose, & Mikkelse, 2019), but it remains unclear how representative these varieties really were.…”
Section: Introductionmentioning
confidence: 99%
“…In a further screening experiment with 20 different wheat genotypes, they concluded that ozone tolerance may be related to the breeding method (hybrids being more sensitive), while the ozone concentration at the breeding site did not play a significant role (Biswas et al, 2009). Others reported chamber fumigation experiments, in which the wild ancestor of bread wheat, Aegilops tauschii , was described as ozone‐sensitive and synthetic hexaploid wheat was rather tolerant (Brewster, Hayes, & Fenner, 2019). In addition, different studies tested the ozone responses of a limited number (usually two) of wheat genotypes that were described as tolerant or sensitive (e.g., Feng et al, 2010; Feng, Pang, Kobayashi, Zhu, & Ort, 2011; Hansen, Hauggaard‐Nielsen, Launay, Rose, & Mikkelse, 2019), but it remains unclear how representative these varieties really were.…”
Section: Introductionmentioning
confidence: 99%